2010
DOI: 10.1271/bbb.90705
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fucoidan-Specific Antibody and Measurement of Fucoidan in Serum and Urine by Sandwich ELISA

Abstract: Fucoidan exhibits various biological properties. We raised a novel antibody against fucoidan extracted from Cladosiphon okamuranus and developed a sandwich ELISA method to measure fucoidan. The fucoidan antibody was specific and did not cross-react with other polysulfated polysaccharides. Fucoidan recovery from serum and urine by ELISA was 86-113%. Intra-and inter-assay CVs were 1.5-13.4%. Assay linearity was maintained after 3-fold dilution of each sample with phosphate-buffer saline (PBS). In the serum and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
85
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 24 publications
2
85
5
4
Order By: Relevance
“…The method that used methylene blue staining of fucoidan blotted on a membrane measured in excess of 1 µg/spot (Lee et al 2012), while Mizuno et al (2009) reported a standard curve at fucoidan concentrations above 5 ng µl −1 using the competitive ELISA method. On the other hand, the sandwich ELISA method described by Tokita et al (2010) showed higher sensitivity (LOD, 0.2 ng ml −1 ) than ours. The standard curve generated with our method showed a 50-fold linear dynamic range, which was wider than any reported to date; 20-fold (Lee et al 2012), 10-fold (Mizuno et al 2009), 18-fold (Tokita et al 2010).…”
Section: Notecontrasting
confidence: 71%
See 3 more Smart Citations
“…The method that used methylene blue staining of fucoidan blotted on a membrane measured in excess of 1 µg/spot (Lee et al 2012), while Mizuno et al (2009) reported a standard curve at fucoidan concentrations above 5 ng µl −1 using the competitive ELISA method. On the other hand, the sandwich ELISA method described by Tokita et al (2010) showed higher sensitivity (LOD, 0.2 ng ml −1 ) than ours. The standard curve generated with our method showed a 50-fold linear dynamic range, which was wider than any reported to date; 20-fold (Lee et al 2012), 10-fold (Mizuno et al 2009), 18-fold (Tokita et al 2010).…”
Section: Notecontrasting
confidence: 71%
“…On the other hand, the sandwich ELISA method described by Tokita et al (2010) showed higher sensitivity (LOD, 0.2 ng ml −1 ) than ours. The standard curve generated with our method showed a 50-fold linear dynamic range, which was wider than any reported to date; 20-fold (Lee et al 2012), 10-fold (Mizuno et al 2009), 18-fold (Tokita et al 2010). …”
Section: Notecontrasting
confidence: 71%
See 2 more Smart Citations
“…It has been long believed that fucoidan, with a high molecular weight, is hardly absorbed in the human digestive system due to a lack of digestive enzymes for fucoidan. Intestinal absorption of fucoidan from Okinawa mozuku has been demonstrated in humans and rats (18,19); however, it is unclear whether fucoidan in mozuku can be absorbed after digestion of mozuku.…”
mentioning
confidence: 99%